Genetics plays a limited role in predicting chronic obstructive pulmonary disease treatment response and exacerbation. (October 2021) - Hosking, Louise; Yeo, Astrid; Hoffman, Joshua; Chiano, Mathias; Fraser, Dana; Ghosh, Soumitra; Lipson, David A.; Martin, Neil; Condreay, Lynn D.; Cox, Charles; St Jean, Pamela
Abstract: Background: Combination treatments, targeting multiple disease processes, benefit subjects with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). However, predicting treatment response and exacerbation risk remain challenging. Objective: To identify genetic associations with AECOPD risk and response to combination therapy (fluticasone furoate, umeclidinium bromide and vilanterol). Methods: The genetic basis of AECOPD disease was investigated in 19, 841 subjects from 23 clinical studies and 2 disease cohorts to identify exacerbation disease targets. AECOPD pharmacogenetic effects were examined in 8439 moderate to severe COPD patients with exacerbation rate, lung function and quality of life endpoints; results were followed up in an additional 2201 subjects. Results: We did not identify significant associations in the AECOPD disease analysis. In the AECOPD pharmacogenetics analysis, rs56195836 ( MAPK8 ) was significantly associated with moderate to severe exacerbation rate in subjects on fluticasone furoate with baseline blood eosinophils ≥150 cells/μl ( P = 1.8 × 10 −8 ). Post-hoc, one variant was associated with on-treatment moderate to severe exacerbation rate stratifying by exacerbation history. AZU1 rs1962343 was significantly associated in subjects with frequent moderate exacerbation history when treated with fluticasone furoate/vilanterol ( P = 1.1 × 10 −8 ). Neither of these signals was supported in independent follow-up. Conclusion: Common genetic variants do not play major roles in AECOPD disease nor predict response to triple therapy or its components in moderate to very severe COPD. Highlights: Triple therapy is recommended for managing acute exacerbations in COPD. Predicting treatment response and exacerbation risk, however, remains challenging. Genetics are implicated in COPD disease risk. Genetics do not predict response to FF/UMEC/VI, UMEC/VI, FF/VI, FF, UMEC or VI.